Match-related performance in mixed martial arts athletes: a technical variability analysis - Carvalho, R.; Novaes, P.; Kons, R. L. (Sport Sciences for Health, 2023)
This study aimed to explore the technical variability index considering different years and technical expertise profiles in high-level MMA athletes. 44 fights from UFC and Pride`s events, and also taken from public websites, were analyzed. These videos were purposely chosen considering the official MMA fighting years of the 1990s, the 2000s, 2010s, and the 2020s. In addition, a comparative analysis was performed considering grapplers and strikers MMA athletes. The variability index was measured based on the attack variability, kicks per knockout, punches per knockouts, groundwork transition to knockouts, and index of qualitative variation (IQV). One-way analysis of variance (ANOVA) and Tukey post hoc test were used to compare the variability index of MMA athletes between different years and the Student T test t test was used for comparison according to the grapplers and strikers with the level at significance at 5%. The main results demonstrated a difference for IQV, higher in the 2020s compared to 2010 (p = 0.019) and kick per knockouts and punches per knockouts for strikers compared to the grappling groups (p = 0.047, p = 0.032 respectively). Based on these results, we concluded that technical variability in MMA can change over the years and the strikers` group have a higher punch and kick variability actions compared to the grapplers, due to the profile of the fight.